Neuropathic pain and psychological morbidity in patients with treated leprosy: a cross-sectional prevalence study in Mumbai. - Estrella Lasry-Levy; Aki Hietaharju; Vivek Pai; Ramaswamy Ganapati; Andrew S C Rice; Maija Haanpää; Diana N J Lockwood (Public Library of Science (PLoS), 2011)
BACKGROUND: Neuropathic pain has been little studied in leprosy. We assessed the prevalence and clinical characteristics of neuropathic pain and the validity of the Douleur Neuropathique 4 questionnaire as a screening tool for neuropathic pain in patients with treated leprosy. The association of neuropathic pain with psychological morbidity was also evaluated. METHODOLOGY/PRINCIPAL FINDINGS: Adult patients who had completed multi-drug therapy for leprosy were recruited from several Bombay Leprosy Project clinics. Clinical neurological examination, assessment of leprosy affected skin and nerves and pain evaluation were performed for all patients. Patients completed the Douleur Neuropathique 4 and the 12-item General Health Questionnaire to identify neuropathic pain and psychological morbidity. CONCLUSIONS/SIGNIFICANCE: One hundred and one patients were recruited, and 22 (21.8%) had neuropathic pain. The main sensory symptoms were numbness (86.4%), tingling (68.2%), hypoesthesia to touch (81.2%) and pinprick (72.7%). Neuropathic pain was associated with nerve enlargement and tenderness, painful skin lesions and with psychological morbidity. The Douleur Neuropathique 4 had a sensitivity of 100% and specificity of 92% in diagnosing neuropathic pain. The Douleur Neuropathique 4 is a simple tool for the screening of neuropathic pain in leprosy patients. Psychological morbidity was detected in 15% of the patients and 41% of the patients with neuropathic pain had psychological morbidity.